A Dresser Drawer Method of Managing Insect and Mite Resistance in Ornamentals - James F. Price; Curtis A. Nagle (EDIS)
ENY-750, a 2-page fact sheet by James F. Price and Curtis A. Nagle, describes a dresser drawer method to develop pesticide rotation plans that can extend the useful lives of pesticides. Published by the UF Department of Entomology and Nematology, July 2008.